Implementasi Otonomi Daerah: Tantangan dan Peluang bagi Pemerintah Daerah dalam Meningkatkan Pelayanan Masyarakat dan Kualitas Hidup Warga - Indra Prayoga Yuspika; Riyan Saputra; Muhammad Yazid Zidan; Khikmawanto Khikmawanto (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This research explores how decentralization policies contribute to improving the quality of public services at the local government level. A qualitative descriptive approach was applied by collecting data through interviews, field observations, and document reviews in several regional government institutions that have implemented delegated authority. The findings reveal that decentralization can enhance service delivery when supported by effective decision-making processes, fair allocation of resources, and the ability of institutions to respond to community needs. Nevertheless, the outcomes largely depend on the readiness of institutions, the capability of human resources, and the consistent application of transparency and accountability principles. In practice, several obstacles remain, including bureaucratic inefficiencies and limited coordination between administrative units, which may reduce policy effectiveness. To address these issues, strengthening institutional capacity, improving organizational structures, and promoting good governance are essential. Furthermore, encouraging greater public involvement is considered important to ensure that public services become more adaptive, transparent, and aligned with societal needs.